The scientific efforts of a professor of Andalusian literature Dr. Hamida Al-Baldawi: An analytical study - Reda, Esraa Abdel (Al-Adab Journal, 2022)
The subject of our study concerns the literary and scientific efforts of acontemporary Iraqi academic researcher specializing in Andalusian literature, as she has published a lot of research and books within her scientific specialization, as well as the scientific production of specializations close to her precise specialization, Professor Dr. Hamida Saleh Mahdi Al-Baldawi.the aimBeing aware of its published and printed efforts in this field, and getting acquainted with its style and literary importance for researchers and readers.Our study was limited to an analysis of samples of its research output in authoring and publishing according to the years of research, due to the abundance of production that it enjoyed throughout its teaching and research period (may God extend its lifetime). Style and approach, it has adopted the literary and artistic style in its scientific and academic method for study and analysis, so that its product has a literary taste and a cognitive material and is a mark in the world of scientific creativity and cognitive composition.The researcher, Dr. Hamida Al-Baldawi, is considered a second generation of Andalusian literature historians, investigators and scholars of Andalusian heritage and its publication. By presenting, studying and analyzing many knowledge and literature regarding this heritage.In my opinion, I tried to fulfill what Professor Dr. Hamida Al-Baldawi deserves.